Age‐ and sex‐mediated differences in T lymphocyte populations of kidney transplant recipients. (27th September 2021) - Dziarmaga, Robert; Ke, Danbing; Sapir‐Pichhadze, Ruth; Cardinal, Héloïse; Phan, Véronique; Piccirillo, Ciriaco A.; Mazer, Bruce; Foster, Bethany J.
Abstract: Background: Graft failure rates increase through childhood and adolescence, decline in adulthood, and are higher in female than male kidney transplant recipients (KTR) until middle age. We aimed to describe age‐ and sex‐related differences in T‐cell subsets among KTR to determine which differences may help to explain the differences in kidney graft failure rates. Methods: Effector T (Teff)‐cell and regulatory T (Treg)‐cell phenotypes in PBMCs from healthy controls and KTR, who were at least 1 year post‐transplant with stable graft function under immunosuppression, were analyzed by flow cytometry. The effects of age, sex, and status (KTR or control) were analyzed using linear regressions. Results: We enrolled 20 male and 21 female KTR and 20 male and 20 female controls between 3 and 29 years of age. CD3+ T‐cell frequencies were not associated with age or sex but were higher in KTR than controls. There were no differences in CD4+ and CD8+ frequencies. Th1 (IFNγ+ IL‐4− IL‐17A−) and Th17 (IL‐17A+) frequencies within the CD4+ T‐cell population were higher at older ages. The frequencies of FOXP3 + Helios + Treg cells in CD4+ CD25+ CD127− T cells were lower in females than males and in KTR than controls. Conclusions: Increasing frequencies of Th1 and Th17 cells with increasing age mirrors the increasing graft failure rates from childhood to young adulthood. Importantly, sex differences in frequencies of circulating Treg cells may suggest a role in the sex differences in graft failure rates.